Islam, Gender, and Social Change: By Yvonne Yazbeck Haddad and John L. Esposito (eds.), (New York and Oxford: Oxford University Press, 1997, 259 pp.) (American Journal of Islam and Society, 2000)
The anthology, Islam, Gender and Social Change, starts with an introductionby Professor John Esposito, one of the coeditors, and it continues with an overarchingchapter "Islam and Gender: Dilemmas in the Changing Arab World" by the other coeditor, Professor Yvonne Yazbeck Haddad. The introductiongives a short survey of gender issues in Islamic history and it points out thatreforms in women’s issues have more often than not been a State rather than agrassroots concern. The strength of the introduction is that in contrast to manyof the other articles in this volume, it takes into account not only the feministpoint of view on gender but deals with the various views that exist in Muslimsociety.Haddad’s chapter introduces the first part of the anthology titled “Islam,Gender, and Social Change: A Reconstituted Tradition,” which gives the readera short survey of the modem challenges facing Arab society. She sees themain factors of change in the Arab world as the economic fluctuations of the1970s and 1980s: labor migration, women’s entrance into the labor market,State ideology and politics, the Islamic movement’s role in society, UnitedNations’ recommendations, and input from Western feminist movements. Sofar, so good; however, in her following comments, Haddad has a tendency tovictimize Arab Muslim women, particularly the religious-oriented- viewpointwhich, as a researcher on the Muslim world, I cannot always agree with.This victimization is partly a result of how Muslim women are often describedfrom an outsider’s perspective, either from a Western or a secular Muslim pointof view. Victimization of Muslim women is not only a feature in Haddad’s articlebut also in many of the other articles in this book. Interestingly, even thefew Muslim contributors do not have a particular Islamic outlook; rather, theyare part of a Western research paradigm. The fact that Islamic-oriented Muslimwomen are generally defined within a frame of Western research traditionsreinforces, on the one hand, attitudes of “we” and “them” and, on the other, thenotion that these women are victims rather than women responsible for theirown lives ...